Decanoato de Nandrolona associado ao exercício físico de intensidade moderada: caracterização dos efeitos gastrintestinais crônicos em ratos - Hauschildt, Andrieli Taise (2024)
Anabolic-androgenic steroids use associated with physical exercise has several acute and chronic side effects, however its repercussion on the gastrointestinal tract remains unknown. Thus, we aimed to establish the effects of nandrolone decanoate treatment and moderate physical exercise on different gastrointestinal parameters in rats. Male Wistar rats were used, divided into 4 groups: Sedentary Control (CS), Exercise Control (CE), Sedentary Anabolic (AS) and Anabolic Exercise (AE). Animals received nandrolone decanoate (5 mg/kg) or vehicle (0.2 mL of peanut oil) intramuscularly twice a week for 8 weeks. For physical training, the motorized treadmill running protocol was adopted. Initially, all animals went through an adaptation period and the Maximum Capacity Test was performed to determine the training intensity threshold. After adaptation, the exercised animals were subjected to running sessions at 60% of maximum speed, 5 days/week for 8 weeks. Sedentary animals were exposed to the treadmill (5 minutes at 5 m/min) once a week. On days 0, 3, 7, 14, 28, 42 and 56 of the experimental protocol, we evaluated gastric emptying of a liquid (EGL) and a solid (EGS) meal using the 13C breathing test and body composition using the bioimpedance method. At the end of 56 days of protocol, intragastric pressure and volume, intestinal transit and both morphometry and in vitro contractility from the antrum, fundus and duodenum were measured. Data normality was analyzed by Shapiro-Wilk and the ANOVA (Tukey's posthoc test) or Kruskal-Wallis (Dunn's posthoc test) tests were applied, differences being significant at p<0.05. As result, serum lactate was increased in both exercise groups. As main results, the CE group showed increase in serum lactate, reduced fat mass and increased fat-free mass and body water content; transiently accelerated the EGL; increased amplitude and decreased frequency of gastric contractions; The AS group showed transient effect in body composition by decreasing fat mass, increasing fat-free mass and total body water content, which were reversed over time; acutely and chronically accelerated gastric emptying; increased amplitude and decreased frequency of gastric contractions; fastened intestinal transit; and enhanced carbachol and sodium nitroprusside responsiveness; In AE animals the GE of liquid and solid was faster, gastric fundus distensibility was improved and gastric contractions showed higher amplitude and lower frequency. Thus, nandrolone decanoate had a dual effect on the body composition, which seems dependent on the treatment time. In gastrointestinal parameters, nandrolone decanoate acts by intensely accelerating gastric emptying, likely through greater excitability mediated by muscarinic receptors in the gastric fundus and enhanced duodenal relaxation induced by nitric oxide pathway.